Mehrsprachigkeit am Arbeitsplatz - MATTICCHIO, ISABELLA; Melchior, Luca (Frank & Timme, 2021)
Communication at work as well as multilingualism, language policy and language politics are increasingly in the focus of linguistic research. Global division of labor, internationalization of labor and trade markets, mobility of highly skilled and unskilled workers, and commodification of language as a product have all played their part. The authors of this book outline the complexity and breadth of the research field: from language courses for asylum seekers to integrate them into the labor market, to linguistic diversity in school social work and competence profiles for lay interpreters in professional contexts, to linguistic practices in the highly internationalized world of soccer and the preconditions of successful communication in the multilingual environment of EU institutions. The contributions offer insights into existing practices, identify challenges, and present possible solutions.